Control Using Lookup Table on Dual Fuel Diesel Engines - Mardiyanto, Ignatius R; Indriyani, Indriyani; Manunggal, Bambang Puguh (INTEK: Jurnal Penelitian, 2020)
Concerns about the availability of fuel oil reserves and air pollution have encouraged innovation to use of alternative fuels in diesel engines. Single fuel Diesel engines modified with a dual fuel, which is a mixture of diesel and gas. The problem of using mixed fuels is that the flashpoint of natural gas must meet the ignition requirements on diesel engines. The consumption of gas fuel in diesel engines, by the load, can continue to work using dual fuel. In this research, the gas fuel supply to control pattern used of dual-fuel with adjusted to the diesel engine load. The lookup table control method, one of the branches of expert system control, apply to change the valve opening of the gas valve. The efficiency of the control results being slightly lower than if manually controlled but still higher than if the fuel only uses diesel fuel.